1999
DOI: 10.1063/1.125498
|View full text |Cite
|
Sign up to set email alerts
|

Efficient route to large arrays of CNx nanofibers by pyrolysis of ferrocene/melamine mixtures

Abstract: We report a high-yield route to two-dimensional arrays (<400×400 μm2) of aligned C49Nx (x⩽1) nanofibers (<100 nm o.d.; <60 μm length), by pyrolyzing mixtures of ferrocene and melamine at 950–1050 °C under an Ar flow. The fibers exhibit unusual interlinked stacked-cone morphologies, ascribed to the presence of nitrogen. High-resolution electron energy-loss spectroscopy of the individual fibers reveals a 2% nitrogen content with ionization energies mainly at ∼400.9 eV, corresponding to N bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
158
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 247 publications
(171 citation statements)
references
References 21 publications
12
158
0
1
Order By: Relevance
“…Their low-dimensional structure does not provide an energetically favorable environment for most impurity atoms. Fortunately, there are two promising exceptions, boron [2] and nitrogen [3], both of which seem able to reside within the carbon lattice.…”
mentioning
confidence: 99%
“…Their low-dimensional structure does not provide an energetically favorable environment for most impurity atoms. Fortunately, there are two promising exceptions, boron [2] and nitrogen [3], both of which seem able to reside within the carbon lattice.…”
mentioning
confidence: 99%
“…This technique has been recently described [17,18]. The produced material consists of carpet-like structures containing highly oriented nanotubes/nanofibres of uniform diameter and length.…”
mentioning
confidence: 99%
“…As will be seen later, we attribute such holes to lattice discontinuities with nitrogen decoration. High resolution electron energy loss spectroscopy (HREELS) studies of these and similar materials reveal the incorporation of N within the graphene lattice at levels between 2 % and 10 % (atom percent) [17][18][19][20][21].…”
mentioning
confidence: 99%
“…The diameters of the nanotubes are varying in between 30 and 60 nm. It has been suggested that bamboo-shaped morphologies arise from the incorporation of pyridine-like N atoms within the carbon framework [30][31][32]. Also, no encapsulated metal particle was found inside the nanotubes.…”
Section: C-n Nanotubesmentioning
confidence: 99%